PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS PLATFORM GENIALLY PADA MATERI TEKS DESKRIPSI SISWA KELAS VII SMP - Rina Marianti; Silvia Permatasari; Zulhafizh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the validity level of interactive learning media based on the Genially platform for descriptive text material for seventh-grade junior high school students. The research method used is Research and Development (R&D) with the ADDIE model. After the development process, the learning media was validated by three validators: a material expert, a media expert, and a language expert. The research instrument used was a validation sheet, which was then analyzed to obtain a validation score. Based on the data analysis results, the interactive learning media based on the Genially platform was declared valid with an average validation percentage of 91%, thus categorized as highly valid. Therefore, the Genially-based learning media for teaching descriptive texts is considered suitable for use in the teaching and learning process by both students and teachers.